MANAJEMEN PROGRAM VOCATIONAL LIFE SKILL PONDOK PESANTREN - Prayoga, Ari; Jahari, Jaja; Fauziah, Mutiara (J-MPI (Jurnal Manajemen Pendidikan Islam), 2019)
Archiving and reporting of the progress of the implementation of vocational programs have not been implemented properly so that the evaluation phase was not well coordinated. Pesantren in its development are not only religious education institutions but also functioned as non-formal education to educate and guide students to have vocational life skills that match their interests and talents. This study aims to uncover the processes of planning, organizing, implementing and monitoring life vocational programs at Baitul Hidayah Islamic Boarding School in Bandung. The research method used is qualitative. The results showed; first, planning is carried out at the beginning of the academic year of pesantren learning; secondly, organizing was divided into 3 coordinators: agriculture and animal husbandry, electricity and water engineering mechanics, buying and selling and trading; third, the implementation is carried out by giving field assignments directly by tutors to students consisting of 80% practice and 20% theory; fourth, supervision is carried out by the field coordinator through the achievement of field assignments and oral and written reports from each field by students.